Answer :


(taking LCM)


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 16; b = - 8 ;c = 1


= 16.1 = 16


And either of their sum or difference = b


= - 8


Thus the two terms are - 4 and - 4


Sum = - 4 - 4 = - 8


Product = - 4. - 4 = 16




4x(4x-1)-1(4x-1) = 0


(4x-1)(4x-1) = 0


(4x-1) = 0 or (4x-1) = 0



The equation has repeated roots


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses